Analysis of Silver Ink Bow-Tie RFID Tag Antennas Printed on Paper Substrates - Sari Merilampi; Leena Ukkonen; Lauri Sydänheimo; Pekka Ruuskanen; Markku Kivikoski (International Journal of Antennas and Propagation)
In this study, polymeric silver inks, paper substrates, and screen printing were used to produce prototype Bow-Tie tags. Because of increasing interest in applying passive UHF-RFID systems in paper industry, the Bow-Tie antenna used in this study was designed to work through paper. The maximum reliable read ranges of the tags were measured thorough stacked paper and also in air. The analysis and functioning of the antenna design are also discussed. All inks and paper substrates were suitable as antenna material and the prototype tag antennas had good reading performance. The maximum reliable read ranges were quite the same as for copper and aluminum tags studied elsewhere. This means that printed UHF tags are competitive solutions for the identification of simple mass products.